Does Academia Still Call? Experiences of Academics in Germany and the United States - Ariane Berthoin Antal; Jan-Christoph Rogge (Minerva, 2020)
Given the significant transformations underway in academia, it is pertinent to ask whether the traditional notion of entering the profession in response to a calling is still relevant. This article draws together hitherto unconnected strands of German and Anglo-Saxon literature on callings, then analyzes biographical narratives of 40 social scientists in Germany and the United States. The comparative analysis of the timing, sources, and nature of the respondents' decision to become academics finds that almost all exhibit a calling orientation. However, their responses no longer correspond to the classical, passive notion; instead, callings in academia have become agentic. In the context of a wider societal trend to self-realization, academia has been transformed to an activity that people pursue because they want to rather than because destiny or an external force pushes them to make such a commitment. The recognition of the social nature of callings is underscored by the significance of professional mentors and family. The unexpected predominance of similarities in the cross-national comparison of calling orientation suggests that the internationalization of academic standards and procedures and the high level of competition for few positions in both contexts may outweigh the effects of culture and tradition.
Keywords: 300; academic career; calling; agentic; Max Weber; vocation; meaningful work